Lavoisier nos livros didáticos: uma análise à luz da História da Ciência - Santos, Ana Flavia (2015)
This work takes as its starting point the observation that the High School Chemistry textbooks suggested by the PNLD (Textbooks Brazilian National Program) often relate, Lavoisier, the Mass Conservation Law and the origins of Modern Chemistry. With the main purpose of analyzing this relation, the textbooks statements were confronted with studies developed by historians of science in the current historiographical perspectives. Besides, the Elementary Treatise of Chemistry was used as a research original source, focusing mainly on the ideas about the caloric that were undertaken by Lavoisier and Laplace, which had a major role in Lavoisier s conceptions about matter and its transformations. Other ideas were also approached involving the transformations of the matter in the eighteenth century, based on current studies of historians of chemistry. Thus, it was possible to analyze the aspects of the construction of these recurrent ideas on the role of Lavoisier in the birth of modern chemistry . This work has been developed as part of the "History of science and education: interdisciplinary approaches in Higher Education (diagnosis, continuous and specialist training for teachers)", Supported by the Centre for Education Program - OBEDUC (CAPES / INEP process 23038.002603 / 2013 -47)